Antinociceptive activity of standardized extract of Bacopa monnieri in different pain models of zebrafish. (10th January 2022) - Sharma, Mahima; Gupta, Pankaj Kumar; Gupta, Pankaj; Garabadu, Debapriya
Abstract: Ethnopharmacological relevance: Bacopa monnieri L. (Scrophulariaceae) is commonly known as Brahmi and traditionally used as a neuroprotective herbal medicine. Recently, Bacopa monnieri exhibited significant therapeutic activity against animal model of neuropathic pain. However, the therapeutic potential of methanolic extract of Bacopa monnieri in experimental animal model is yet to establish. Aim of the study: The present study was designed to evaluate the anti-nociceptive potential of standardized methanolic extract of Bacopa monnieri in experimental adult zebrafish ( Danio rerio ) model of pain. Materials and methods: The methanolic extract of Bacopa monnieri (BME) was standardized to bacoside-A using chromatographic method. Subsequently, BME (0.75, 1.25 and 5.0 mg/ml) was evaluated for anti-nociceptive activity using adult zebrafish model. Results: Standardized BME showed antioxidant effect through radical quenching activity in in vitro study. BME at 1.25 mg/ml significantly decreased the nociceptive effect induced by different noxious agents like acetic acid where as BME at 2.5 mg/ml exhibited significant antinociceptive activity against glutamate, formalin, capsaicin, cinnamaldehyde when compared to control and sham group animals. Conclusion: BME exerted antinociceptive activity in adult zebrafish. It could be presumed that BME may involve glutamatergic receptor, ASIC and TRP channel activity in its anti-nociceptive effect. BME could be considered as a potential therapeutic option in the management of pain. Graphical abstract: Image 1 Highlights: The methanolic extract of Bacopa monnieri (BME) was standardized to Bacoside-A. BME exhibited antinociceptive activity in acetic acid treated adult zebrafish. BME exhibited antinociceptive activity in glutamate and formalin treated zebrafish. BME showed antinociceptive effect in capsaicin and cinnamaldehyde treated animals. BME could be a potential therapeutic option in the management of pain.